Chemical variation on one single basaltic lava flow from Terceira Island (Azores archipelago): zoned magma chamber or lava flow fractionation? - Madureira, Pedro (2005)
Several processes controlling magma rheology, crystallisation and cooling are believed to occur in magma chambers in order to generate layered intrusions (e.g. Bottinga and Weil 1970; McBirney, 1996). These processes are also expected to develop an important role in the differentiation of cogenetic lava series through fractional crystallisation. For Terceira island, several rock samples coming from one single basaltic lava flow were analysed. The lava was erupted from the Algar do Carvão scoria cone (approximately 2000 years ago, Zbiyszewski, 1971) forming an extensive stream of lava that overflows the Guilherme Moniz Caldera and extends towards NE and SSE over more than 10 km. It has a porphyritic texture (3% phenocrysts) mainly composed by phenocrysts of olivine ± clinopyroxene and rare plagioclase. The same phases are present in the groundmass which is dominated by plagioclase and opaque minerals. Whole rock analyses display chemical variations within this lava flow that are correlated with the distance to the vent. Compatible elements are enriched in samples collected near the vent while incompatible elements are preferentially concentrated in samples collected far away from the vent. These results are in agreement with the possible existence of a zoned magma chamber or, alternatively, they could be interpreted as a result of fractionation promoted by lava flow. Some constraints will be discussed in order to validate one of the proposed models.